Epidemiological characterization of chronic myeloid leukaemia patients at an oncologic centre: A retrospective observational study - Ana Maria Meireles; Rita Calisto; Maria José Bento; Pedro Martinho Gouveia; Susana Bizarro; Manuel Teixeira; Cláudia Moreira; Ana Espírito Santo; Mário Mariz (Hematology, Transfusion and Cell Therapy)
Background: The chronic myeloid leukaemia population, treatment patterns and responses in Portugal are unknown. The aim of this study is to describe these features in a Portuguese reference centre. Methods: A retrospective cohort study included patients with chronic myeloid leukaemia, treated between 2012 and 2022 at the Instituto Português de Oncologia of Porto. Data were obtained from the Cancer Registry of the institution and clinical records. Variables included demographic data, treatments administered, responses (hematologic, cytogenetic, major and deep molecular responses), adverse events, and survival. Patients without available data, those treated in a clinical trial context, and those admitted only for hematopoietic transplantation were excluded. Results: Ninety-nine patients were included in this study, with a median age of 52 years (range: 7–84 years) at diagnosis. The first-line treatment was imatinib in 96 patients however 33 required second-line with dasatinib, and 17 discontinued treatment while maintaining response. Regarding responses, 95 (96 %) patients achieved cytogenetic response, 90 (94 %) achieved major molecular response, and 71 (72 %) achieved deep molecular response. At three months, the early molecular response rate was 77 %. At 12 months of treatment, of the 67 patients with response evaluation, 93 % achieved complete cytogenetic response and 49 % major molecular response. Both imatinib and dasatinib were well tolerated. The median follow-up was eight years. The five-year overall survival was 96 %. Conclusion: This study is the first to characterize chronic myeloid leukaemia patients at a Portuguese centre. The patient characteristics, responses, and overall survival were within the expected range according to the literature. This study confirms the good prognosis of chronic myeloid leukaemia and the good responses using imatinib as first-line treatment.